KEDUDUKAN PEREMPUAN HINDU DALAM KITAB SARASAMUCCAYA (KAJIAN ETIKA HINDU) - Ni Made Ayu Erna Tanu Ria Sari (Purwadita : Jurnal Agama dan Budaya, 2019)
Knowledge of the position of women in society is of particular concern, especially forcommunity appraisers, because in general the position of women in society can be seen asbiased to know the back and forth of society. Knowledge of the position of women especially inHindu society, provides explanations that are very interesting. In the discussions that have beencarried out, our knowledge of women and the position of women or community attitudes towardswomen is very little known to us. But considering the issue of the position of women in society, itis indeed things that provide a mirror of the position of progress in society. On the interpretationof the contextually that Sarasamuccaya text blatantly blatantly discriminates against women asobjects that must be kept away from men, but this is a discourse or advice that leaders must beexemplary as explained in the concept of the Hindu leadership trilogy which is known as sungtuladha, ing mad mangun karso lan tut wuri handayani means that leaders must be mediatorsand motivators for subordinates and their people. That if you want to be successful, then stayaway from women who are meant here that stay away from women who are not theirs because inthe bond of men and women must be a legitimate relationship because this bond will be interwovenin a marriage that is essentially sacred or sacred.